The impact of physiological and parafunctional posterior occlusal forces on experimental Ti- 15Zrsupracrestal dental implant – a finite element analysis - Bokor, Brigitta; Objelean, Adriana; Bran, Simion; Campian, Radu Septimiu; Vilău, Cristian (Medicine and Pharmacy Reports, 2025)
Aim of the study. This study aims to evaluate and compare the stress distribution patterns of two experimental tissue-level, convergent collar implants (one made of Ti- 6Al-4V (control) and the other of Roxolid-based (Ti-15Zr) material) using 3D finite element analysis (FEA) under various simulated masticatory conditions. Methods. A 3D finite element model replicating a tissue-level implant with convergent neck design was developed in ANSYS software, incorporating both cortical and trabecular bone geometry. Implants made of Ti-6Al-4V-Grade 5 and Roxolide-type- Ti-15Zr alloy were simulated under axial (0°) and oblique (45° angle) loading forces (50 N, 200 N, 300 N, and 400 N). The von Mises equivalent stress distribution was calculated to assess the biomechanical performance. Results. Under masticatory forces simulation, titanium-alloy implants exhibited maximum stress values (400 N) of 260.38 MPa under axial load and 536.2 MPa under oblique load. Ti-15Zr implants exhibited a slightly lower peak stress of 506.95 MPa under a load of 400 N at a 45° inclination and 240.81 N under axial load. Based on 3D finite analysis, the stress distribution maps showed higher concentration in the implant–abutment connection and the cervical region, particularly under oblique loading. Conclusions. Although titanium implants exhibited higher stress limits, Ti-15Zr implants showed biomechanical stability under oblique simulated forces. Ti- 15Zr implants exhibited a more uniform stress distribution with a reduced peak concentration.